Объяснение:
(n+6)²=n²+12n+36
(13h+1)²=169h²+26h+1
(4-3y)²=16-24y+9y²
(2k-8)²=4k²-32k+64
(3c+7d)²=9c²+42cd+49d²
(9a+t)²=81a²+18at+t²
(k-8)²=k²-16k+64
(5-7m)²=25-70m+49m²
(13p-3)²=169p²-96p+9
(2f-10a)²=4f²-40af+100f²
(-3h+7)²=9h²-42h+49
(-10x-y)²=100x²+20xy+y²
(с-10)²=c²-28c+100
(11х+4)²=121x²+88x+16
(6+2y)²=36+24y+4y²
(4k-3)²=16k²-24k+9
(3c+2d)²=9c²+12cd+4d²
(8х-3у)²=64x²-48xy+9y²
(3а-5в)²=9a²-30aв+25в²
(7с-2m)²=49с²-28сm+4m²
(в+8)²=a²+16a+64
(12h+2)²=144h²+48h+4
(5-2y)²=25-20y+4y²
(3k-4)²=9k²-24k+16
(2c+5d)²=4c²+20cd+25d²
(8a+2t)²=64a²+32at²+4t²
ответ: (a+b)(a-b+1)
Объяснение: a²-b²=(a-b)(a+b)
Тогда a²-b²+a+b= (a+b)(a-b+1)